Концепція ризику інвестиційного бізнес-проекту - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Терновський, Володимир Олександрович; Терновский, Владимир Александрович; Ternovsky, Volodymyr; Зайцева, О. І.; Бериславська, А. І. (My University, 2018)
UK: У статті розглянуто концепція ризику інвестиційного бізнес-проекту на основі методів кількісної оцінки. З позиції невизначеності економічного середовища представлено функцію корисності сприйняття ризику для інвестора та використано кумулятивні профілі ризику, які описують альтернативність інвестицій-них бізнес-проектів для забезпечення обсягу поточної вартості чистого грошового потоку. Представлено модель сукупної ризик-компоненти інвестиційного бізнес-проекту в часовому періоді. EN: The concept of risk of investment business project on the basis of effective methods of quantitative assessment is considered in the article. Multifunctionality of the concept «investment business project» defines its essence in two aspects: as a document and as a concrete action of the investor in the realization of their investment intentions. That is, it is a manifestation of the investment initiative of the entity, which involves investing in a particular object of real investment, aimed at realizing a deterministic in time for a particular investment objective and obtaining the planned concrete results. The degree of risk of investment business projects, which has the greatest activity among the subjects of investment activity, is substantiated. From the point of view of the uncertainty of the economic environment, the concept of the function of the usefulness of risk perception for the investor is defined. It is proved that the Monte Carlo simulation method, as a synthesis of sensitivity analysis and scenario analysis methods, allows to determine the optimal and most probable value for the existing statistical apparatus for assessing the variation of risk. Cumulative risk profiles have been used to describe the placement and crossings of alternative investment business projects in or-der to identify the most attractive of them to provide the amount of current value of net cash flows. An aggregate ap-proach to risk assessment of an investment business project that takes into account the beta method or the weighted average cost of capital method is summarized and ordered. The system of aggregate risk components of an investment business project is modulated with a certain probability of its action in time.
The concept of risk of investment business project
Keywords: інвестиційний ризик; інвестиційний бізнес-проект; методи оцінки ризику; результуючий показник; кількісний аналіз ризику; investment risk; investment business project; risk assessment methods; result indicator; quantitative risk analysis